2019
DOI: 10.1200/jco.18.00283
|View full text |Cite|
|
Sign up to set email alerts
|

Microsatellite Instability Is Associated With the Presence of Lynch Syndrome Pan-Cancer

Abstract: PURPOSE Microsatellite instability (MSI) and/or mismatch repair deficiency (MMR-D) testing has traditionally been performed in patients with colorectal (CRC) and endometrial cancer (EC) to screen for Lynch syndrome (LS)–associated cancer predisposition. The recent success of immunotherapy in high-frequency MSI (MSI-H) and/or MMR-D tumors now supports testing for MSI in all advanced solid tumors. The extent to which LS accounts for MSI-H across heterogeneous tumor types is unknown. Here, we establish the preval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
364
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 448 publications
(381 citation statements)
references
References 44 publications
12
364
3
2
Order By: Relevance
“…Highest frequencies have been reported for endometrial (21-30%), colon (up to 19%), and stomach cancer (6-22%), but an increasing number of studies is showing that MSI can be found in virtually all individual cancer types at a frequency of approximately 1%. [7][8][9][10][11][12][13][14][15] Tumor-infiltrating lymphocytes have been linked to tumor phenotype as well as favorable patient outcome or response to therapy in various tumor types. [16][17][18] MSI is associated with a high number of tumorinfiltrating lymphocytes providing indirect evidence for a particular role of the antitumoral immune response in such tumors, presumably due to increased neoantigen production.…”
mentioning
confidence: 99%
“…Highest frequencies have been reported for endometrial (21-30%), colon (up to 19%), and stomach cancer (6-22%), but an increasing number of studies is showing that MSI can be found in virtually all individual cancer types at a frequency of approximately 1%. [7][8][9][10][11][12][13][14][15] Tumor-infiltrating lymphocytes have been linked to tumor phenotype as well as favorable patient outcome or response to therapy in various tumor types. [16][17][18] MSI is associated with a high number of tumorinfiltrating lymphocytes providing indirect evidence for a particular role of the antitumoral immune response in such tumors, presumably due to increased neoantigen production.…”
mentioning
confidence: 99%
“…In a study of .15,000 patients with cancer treated at Memorial Sloan Kettering Cancer Center who had their tumor and matched normal DNA sequenced and tumor MSI status assessed, approximately 5% of 1,048 patients with prostate cancer had MSI-high (MSI-H) or MSI-indeterminate tumors, 5.6% of whom were found to have Lynch syndrome (0.29% of patients with prostate cancer). 23 In another prospective case series, the tumors of 3.1% of 1,033 patients with prostate cancer demonstrated MSI-H/dMMR status, and 21.9% of these patients had Lynch syndrome (0.68% of the total population). 59 In a study of an unselected cohort of 3,607 patients with a personal history of prostate cancer who had germline genetic testing based on clinician referral, 1.7% had germline mutations in PMS2, MLH1, MSH2, or MSH6.…”
Section: Dna Mmr Genesmentioning
confidence: 96%
“…[20][21][22] In addition, prostate cancer has been associated with hereditary breast and ovarian cancer (HBOC) syndrome (due to germline mutations in homologous DNA repair genes) and Lynch syndrome (resulting from germline mutations in DNA mismatch repair [MMR] genes). [23][24][25][26][27] In fact, approximately 11% of patients with prostate cancer and at least 1 additional primary cancer carry germline mutations associated with increased cancer risk. 28 Therefore, the panel recommends a thorough review of personal and family history for all patients with prostate cancer.…”
Section: Prostate Cancer Geneticsmentioning
confidence: 99%
“…Синдром Линча ассоциирован с повышением шанса развития ряда опухолей, составляющих в течении жизни: колоректального рака (до 70 %), рака эндометрия (до 71 %), рака желудка (до 13 %), рака предстательной железы (до 30 %), рака поджелудочной железы (до 4 %), рака яичников (до 20 %), рака молочной железы (до 18 %) [3 -6]. Синдром Линча является причиной MSI лишь у 15 -38 % больных, остальные случаи dMMR обусловлены спорадическими нарушениями, появившимися уже в клетках самой опухоли [7]. Чаще в их основе лежит гиперметилирование промотера гена MLH1, что приводит к «выключению» экспрессии белка.…”
Section: система репарации неспаренных оснований и нарушения ее механunclassified